Methods of fractal analysis applied to STM imaging - Vázquez, L. (1995)
Vapor deposited gold films have been characterized by applying methods of fractal analysis to scanning tunneling microscopy (STM) images. Results from the use of five different methods are in agreement within the limitation of each method. Those methods are suitable to characterize rough surfaces at the nanometer level provided that a large number of images is considered.